Maternal and personal information mediates the use of social cues about predation risk. (8th March 2021) - Winandy, Laurane; Di Gesu, Lucie; Lemoine, Marion; Jacob, Staffan; Martin, José; Ducamp, Christine; Huet, Michèle; Legrand, Delphine; Cote, Julien
Abstract: Organisms can gain information about predation risks from their parents, their own personal experience, and their conspecifics and adjust their behavior to alleviate these risks. These different sources of information can, however, provide conflicting information due to spatial and temporal variation of the environment. This raises the question of how these cues are integrated to produce adaptive antipredator behavior. We investigated how common lizards ( Zootoca vivipara ) adjust the use of conspecific cues about predation risk depending on whether the information is maternally or personally acquired. We experimentally manipulated the presence of predator scent in gestating mothers and their offspring in a full-crossed design. We then tested the consequences for social information use by monitoring offspring social response to conspecifics previously exposed to predator cues or not. Lizards were more attracted to the scent of conspecifics having experienced predation cues when they had themselves no personal information about predation risk. In contrast, they were more repulsed by conspecific scent when they had personally obtained information about predation risk. However, the addition of maternal information about predation risk canceled out this interactive effect between personal and social information: lizards were slightly more attracted to conspecific scent when these two sources of information about predation risk were in agreement. A chemical analysis of lizard scent revealed that exposure to predator cues modified the chemical composition of lizard scents, a change that might underlie lizards' use of social information. Our results highlight the importance of considering multiple sources of information while studying antipredator defenses. Abstract : Prey use information about predation risk to adjust their behavior. Information can be acquired from their parents, from their own personal experience, and from conspecifics. These different sources of cues can provide conflicting information raising the question of how an individual integrates all this information together to produce adaptive antipredator behavior. We found that personal and maternal information interacted to shape individual responses to conspecific cues about predation risk.